2020
DOI: 10.1111/jsr.13102
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioural therapy for insomnia does not appear to have a substantial impact on early markers of cardiovascular disease: A preliminary randomized controlled trial

Abstract: According to the World Health Organization, cardiovascular diseases are the leading cause of death in the world. Therefore, early prevention of these diseases is a public health priority. Epidemiological data suggest that insomnia may be a modifiable risk factor for cardiovascular diseases. A randomized controlled trial in a sample of insomnia patients without cardiovascular disease was conducted to investigate the effects of insomnia treatment on early markers of cardiovascular diseases assessed by 24‐hr ambu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 61 publications
1
14
2
Order By: Relevance
“…Thirdly, part of the treatment components delivered in CBT-C was based on the main evidence-based practice parameters for the psychological treatment of insomnia [ 41 ]. In contrast with our study, none of the studies referred to above [ 45 , 46 ] found benefits of CBT in autonomic cardiac regulation. Jarrin, et al (2016) [ 45 ], performed a secondary analysis of a clinical trial conducted among patients suffering from insomnia after receiving six weekly group sessions of CBT-I [ 65 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Thirdly, part of the treatment components delivered in CBT-C was based on the main evidence-based practice parameters for the psychological treatment of insomnia [ 41 ]. In contrast with our study, none of the studies referred to above [ 45 , 46 ] found benefits of CBT in autonomic cardiac regulation. Jarrin, et al (2016) [ 45 ], performed a secondary analysis of a clinical trial conducted among patients suffering from insomnia after receiving six weekly group sessions of CBT-I [ 65 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, we can make comparisons between our clinical trial and those that have assessed HRV parameters as outcome results after CBT for insomnia delivered among insomnia patients [ 45 , 46 ]. Firstly, autonomic dysregulations in FM patients have similarities with the pattern observed in insomnia patients: increased sympathetic activation and decreased parasympathetic activity during sleep [ 23 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a newly published RCT assessed the short‐term effect of cognitive behavioural therapy for insomnia (CBT‐I) on CV risk factors such as 24‐hr ambulatory blood pressure, heart rate, CRP and N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) in 46 individuals without CVD before and after 8 weeks of CBT‐I therapy. The study found no significant treatment effects on these markers of CVD in those receiving treatment or randomised to waitlist control (Johann et al., 2020). That study did not include individuals at increased risk of CVD or elevated cTnI in their analysis, but reaches the same conclusion as a previous study published in 2017 that CBT‐I did not lower blood pressure in individuals free of known CVD (Mcgrath et al., 2017).…”
Section: Discussionmentioning
confidence: 99%